Sulfur autotrophic filler and preparation method and application thereof

By preparing sulfur self -care filler by preparing sulfur self -care filler by the nano -carbonate carbonate porous carrier of the high ratio surface area and an orderly medium hole structure, it solves the problem of the existing fillers smaller than the surface area, low decentralization and difference in strength. Achieve efficient sulfur self -nitrification and nitrogen dehydration, extend the service life and reduce carbon emissions.

CN116143281BActive Publication Date: 2025-01-28DASMART ENVIRONMENTAL SCI & TECH (BEIJING) CO LTD

Patent Information

Application Number
CN202211740390.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2022-12-30
Publication Date
2025-01-28
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The existing sulfur autotrophic denitrification fillers have small specific surface area, low sulfur dispersion and poor strength, resulting in low denitrification accuracy, load and strength, large mass transfer resistance, and short service life.

Method used

Single sulfur loads are used to prepare sulfur self -supporting fillers through steps, dryness and roasting such as nano -carbonated calcium carbonate porous vector with a high ratio and orderly medium -holy channel structure, and increase the decentralization of sulfur through the impregnation method.

Benefits of technology

It improves the accuracy and load of sulfur self -cultivation and nitrating nitrogen removal, reduce the resistance of quality, prolong the service life of the filler, reduce the amount of carbon emissions, and realize the depth treatment of green and low -carbon sewage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116143281B_ABST
    Figure CN116143281B_ABST
Patent Text Reader

Abstract

The present invention provides a sulfur autotrophic filler and a preparation method and application thereof, and relates to the field of water treatment technology. The sulfur autotrophic filler provided by the present invention comprises a porous carrier and elemental sulfur; the elemental sulfur is loaded on the porous carrier; the porous carrier is mainly prepared from nano-calcium carbonate, a binder and a pore-forming agent. The sulfur autotrophic filler has a high sulfur dispersion, increases the contact surface area between sulfur and the biofilm, reduces the mass transfer resistance in the sulfur autotrophic denitrification denitrification process, and has high denitrification accuracy, denitrification load and strength. The preparation method of the sulfur autotrophic filler provided by the present invention is simple and convenient. By immersing the porous carrier in a solvent containing elemental sulfur, the steric hindrance effect is greatly reduced, and sulfur can be allowed to enter the inner pores of the porous carrier more smoothly, thereby improving the sulfur dispersion, increasing the contact surface area between sulfur and the biofilm, reducing the mass transfer resistance in the sulfur autotrophic denitrification denitrification process, and improving the denitrification treatment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a sulfur autotrophic filler and a preparation method and application thereof. Background Art

[0002] Deep treatment of nitrogen is the top priority in the transformation of sewage treatment standards. At present, biological denitrification is mainly used for sewage treatment denitrification. Denitrification is also called denitrification, which is widely used because of its low cost. As a typical nitrate sewage, the existence of low carbon-nitrogen ratio nitrate sewage is widespread, and the harm it brings to the ecological environment and residents' health is becoming increasingly prominent. Heterotrophic denitrification biological denitrification technology is currently a widely used sewage and wastewater deep denitrification treatment technology, but it requires the addition of an organic carbon source, which is costly, and the dosage is difficult to control, which is easy to cause secondary pollution. In addition, there are problems such as large sludge volume and high disposal cost. As a typical nitrate sewage, the existence of low carbon-nitrogen ratio nitrate sewage is widespread, and the harm it brings to the ecological environment and residents' health is becoming increasingly prominent.

[0003] Sulfur autotrophic denitrification biological denitrification technology is essentially a catalytic reaction, an enzyme catalysis. This technology uses CO2, HCO3 - and CO3 2- As inorganic carbon sources, reduced inorganic substances (including S, S - , S 2- 、S2O3 2- , Fe and Fe 2+ etc.) as electron donors to convert nitrate nitrogen (including NO3 - -N and NO2 - -N) is reduced to nitrogen (N2).

[0004] Sulfur autotrophic denitrification biological denitrification technology is a new type of biological denitrification technology, which refers to the process of sulfur bacteria using CO2, HCO3 - and CO3 2- The process of reducing nitrate nitrogen to N2 using inorganic carbon such as sulfur as a growth carbon source and elemental sulfur, sulfide, sulfite, tetrasulfonate or thiosulfate as an electron donor. This technology can be used in the fields of deep denitrification of municipal sewage, deep purification of polluted surface water environment and remediation of nitrate-contaminated groundwater.

[0005] Redox reaction is a reaction of gaining and losing electrons, which is realized through electron transfer. The reduced substance gains electrons and its valence decreases; the oxidized substance loses electrons and its valence increases. In the process of removing nitrate nitrogen by autotrophic denitrification technology, the electron donor loses electrons and its valence increases; nitrate nitrogen (including NO3 --N and NO2 - -N) gains electrons, and its valence is reduced. In the process of sulfur autotrophic denitrification, nitrate nitrogen (NO3 - -N) through a series of intermediates (NO2 - , NO, N2O) are reduced to N2, mainly through NO3 - →NO2 - →NO→N2O→N2 4 processes. - -N is reduced, NO3 - 、NO2 - , NO, N2O, N2 and NH4 + The valence of N in different nitrides is: +5, +3, +2, +1, 0 and -3. In the oxidation reaction of electron donor sulfide, S - , S 2- 、S、S2O3 2- Unlike H2SO4, the valence of S in sulfides are -1, -2, 0, +2 and +6 respectively.

[0006] Sulfur autotrophic denitrification is a total nitrogen removal technology with relatively low energy consumption and high efficiency, which has attracted extensive attention in recent years. - 、S、S2O3 2- 、S4O6 2- 、SO3 2- All of them can be used as electron donors, but because sulfur is insoluble in water and easy to separate, sulfur is usually selected as the electron donor.

[0007] At present, the most widely used sulfur autotrophic denitrification process for wastewater denitrification is the "Sulfur-Limestone Autotrophic Denitrification" (SLAD) system. The SLAD system is an autotrophic denitrification process using sulfur as an electron donor. It has the advantages of no need for external organic carbon sources, low cost and low sludge production, and has gradually become a research hotspot for deep denitrification.

[0008] In the sulfur-limestone autotrophic denitrification system, when elemental sulfur is used as the electron donor, the overall chemical reaction equation of the sulfur autotrophic denitrification process is shown in formula (1):

[0009] 5S 0 +6NO3 - +2H2O→5SO4 2- +3N2+4H + (1)

[0010] The above reaction process includes the generation process of biomass:

[0011] 1.10S 0 +NO3 - +0.76H2O+0.40CO2+0.08NH4 + →0.08C5H7O2N+1.10SO4 2- +0.50N2+1.28H + (2)

[0012] In the sulfur-limestone autotrophic denitrification system, the principle of limestone (calcium carbonate) providing alkalinity is:

[0013] CaCO3+H + →HCO3 - +Ca 2+ (3)

[0014] HCO3 - +H + →H2CO3 (4)

[0015] H2CO3→CO2+H2O (5)

[0016] The overall reaction equation of formula (3)-(5) is:

[0017] CaCO3+2H + →Ca 2+ +CO2+H2O (6)

[0018] Sulfur autotrophic denitrification technology is a solid-liquid multiphase catalytic reaction. Sulfur is a non-polar substance and is difficult to dissolve in water. The efficiency of sulfur autotrophic filler depends largely on the accessibility of sulfur to the biofilm. In the process of sulfur autotrophic denitrification, the mass transfer efficiency of elemental sulfur from the solid phase to the biofilm surface is the rate-controlling step of the entire reaction process.

[0019] The specific surface area of ​​sulfur autotrophic filler is an important factor restricting the surface reaction rate of sulfur autotrophic denitrification process, because increasing the specific surface area can promote the dissolution of elemental sulfur on the one hand, and promote the effective contact between microorganisms and elemental sulfur on the other hand. Therefore, increasing the specific surface area of ​​sulfur autotrophic filler can significantly improve the denitrification rate of sulfur autotrophic denitrification system.

[0020] At present, there are problems in the autotrophic denitrification technology, such as low denitrification accuracy, denitrification load and intensity.

[0021] In view of this, the present invention is proposed. Summary of the invention

[0022] The first purpose of the present invention is to provide a sulfur autotrophic filler, which loads sulfur on a porous carrier of nano-calcium carbonate with a high specific surface area and an ordered mesoporous channel structure, overcoming the defects of the sulfur autotrophic fillers currently used in engineering, such as small specific surface area, low sulfur dispersion and poor strength, reducing the mass transfer resistance in the sulfur autotrophic denitrification process, improving the denitrification treatment effect, and extending its service life by increasing its strength.

[0023] The second object of the present invention is to provide a method for preparing the above-mentioned sulfur autotrophic filler.

[0024] The third object of the present invention is to provide the use of the above-mentioned sulfur autotrophic filler in sulfur autotrophic denitrification.

[0025] In a first aspect, the present invention provides a sulfur autotrophic filler, comprising a porous carrier and elemental sulfur;

[0026] The elemental sulfur is loaded on the porous carrier;

[0027] The porous carrier is mainly prepared from nano calcium carbonate, a binder and a pore-forming agent.

[0028] As a further technical solution, the mass of the elemental sulfur is 20%-30% of the mass of the porous carrier;

[0029] The mass ratio of the binder to the nano-calcium carbonate is 11.9%-15%; the mass ratio of the pore-forming agent to the nano-calcium carbonate is 6.8%-7.1%.

[0030] As a further technical solution, the binder includes at least one of bentonite, attapulgite, diatomaceous earth, kaolin, argillaceous earth, cement, quartz sand, hydroxypropyl methylcellulose, polyvinyl alcohol, sodium carboxymethyl cellulose, styrene-butadiene rubber powder, latex powder or sesbania powder;

[0031] The pore-forming agent includes at least one of cellulose powder, ammonium bicarbonate, hydroxypropyl methylcellulose, polyvinyl alcohol, sodium carboxymethyl cellulose, styrene-butadiene rubber powder, latex powder or sesbania powder.

[0032] As a further technical solution, the method for preparing the porous carrier comprises: mixing the formulated amounts of nano-calcium carbonate, a binder and a pore-forming agent, and then sequentially forming, drying and calcining to prepare the porous carrier.

[0033] As a further technical solution, the forming method includes disc granulation, extrusion or tableting;

[0034] The molding process also includes adding 8%-20% water by weight of the raw materials.

[0035] As a further technical solution, the drying temperature is 120-150°C;

[0036] The drying time is 3-10 hours.

[0037] As a further technical solution, the calcination temperature is 350-500°C;

[0038] The calcination time is 3-5h.

[0039] In a second aspect, the present invention provides a method for preparing the above-mentioned sulfur autotrophic filler, comprising: immersing the porous carrier in a solvent containing elemental sulfur, and preparing the sulfur autotrophic filler after drying.

[0040] As a further technical solution, the solvent includes carbon disulfide;

[0041] The mass of the carbon disulfide is 2-3 times the mass of elemental sulfur.

[0042] In a third aspect, the present invention provides the use of the above-mentioned sulfur autotrophic filler in sulfur autotrophic denitrification.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The sulfur autotrophic filler provided by the present invention includes a porous carrier and elemental sulfur, wherein the elemental sulfur is loaded on the porous carrier, and the porous carrier has a high specific surface area and an ordered mesoporous channel structure, which can be used as a carrier of elemental sulfur to improve its dispersion; it can also be used as a component to provide alkalinity; it can also be used as a carrier for the growth of sulfur autotrophic denitrifying bacteria, which is conducive to the attachment and growth of negatively charged bacteria and increases the biomass in the system; in addition, the porous carrier also greatly improves the strength of the sulfur autotrophic filler, thereby significantly extending its service life. The sulfur autotrophic filler provided by the present invention has a high sulfur dispersion, increases the contact surface area between sulfur and the biofilm, and reduces the mass transfer resistance in the sulfur autotrophic denitrification process, which is manifested in macroscopically as improving the denitrification accuracy and denitrification load, while improving the strength. Improving the denitrification accuracy means improving the impact resistance; increasing the denitrification load means reducing the amount of filler used, that is, reducing the investment cost; improving the strength means extending the service life of the autotrophic denitrification nanomaterial, that is, reducing the investment cost.

[0045] The preparation method of the sulfur autotrophic filler provided by the present invention is simple and convenient. By immersing the porous carrier in a solvent containing elemental sulfur, the steric hindrance effect is greatly reduced, so that the sulfur can enter the inner pores of the nano-calcium carbonate porous carrier more smoothly and be more evenly dispersed on the inner surface of the nano-calcium carbonate, thereby improving the dispersion of the sulfur, increasing the contact surface area between the sulfur and the biofilm, reducing the mass transfer resistance in the sulfur autotrophic denitrification process, and improving the denitrification treatment effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0047] Figure 1 is the adsorption-desorption isotherm of the sulfur autotrophic filler of Comparative Example 1;

[0048] Figure 2 The pore size distribution curve of the sulfur autotrophic filler of Comparative Example 1;

[0049] Figure 3 is the adsorption-desorption isotherm of the sulfur autotrophic filler in Example 1;

[0050] Figure 4 This is the pore size distribution curve of the sulfur autotrophic filler in Example 1. DETAILED DESCRIPTION

[0051] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0052] In a first aspect, the present invention provides a sulfur autotrophic filler, comprising a porous carrier and elemental sulfur;

[0053] The elemental sulfur is loaded on the porous carrier;

[0054] The porous carrier is mainly prepared from nano calcium carbonate, a binder and a pore-forming agent.

[0055] The sulfur autotrophic filler provided by the present invention includes a porous carrier and elemental sulfur, wherein the elemental sulfur is loaded on the porous carrier, and the porous carrier has a high specific surface area and an ordered mesoporous channel structure, which can be used as a carrier of elemental sulfur to improve its dispersion; it can also be used as a component to provide alkalinity; it can also be used as a carrier for the growth of sulfur autotrophic denitrifying bacteria, which is conducive to the attachment and growth of negatively charged bacteria and increases the biomass in the system; in addition, the porous carrier also greatly improves the strength of the sulfur autotrophic filler, thereby significantly extending its service life. The sulfur autotrophic filler provided by the present invention has a high sulfur dispersion, increases the contact surface area between sulfur and the biofilm, and reduces the mass transfer resistance in the sulfur autotrophic denitrification process, which is manifested in macroscopically as improving the denitrification accuracy and denitrification load, while improving the strength. Improving the denitrification accuracy means improving the impact resistance; increasing the denitrification load means reducing the amount of filler used, that is, reducing the investment cost; improving the strength means extending the service life of the autotrophic denitrification nanomaterial, that is, reducing the investment cost.

[0056] In addition, the application of the sulfur autotrophic filler of the present invention can greatly reduce carbon emissions. The traditional heterotrophic denitrification biological denitrification technology in the sewage treatment process requires the addition of a carbon source; while the autotrophic denitrification biological denitrification technology does not require the addition of an additional carbon source, which greatly reduces carbon emissions and truly achieves carbon reduction. It is a green and low-carbon solution for deep sewage treatment and belongs to green and low-carbon processes and products. The autotrophic denitrification denitrification technology can effectively reduce the carbon source consumption of the traditional biological denitrification technology and has a good place to be used.

[0057] In some preferred embodiments, the mass of the elemental sulfur is 20%-30% of the mass of the porous carrier. This loading amount is reasonable and can ensure sufficient sulfur loading while not affecting the sulfur autotrophic denitrification.

[0058] The mass ratio of the binder to the nano-calcium carbonate may be, for example, but not limited to, 11.9%, 12%, 13%, 14% or 15%;

[0059] The mass ratio of the pore-forming agent to the nano-calcium carbonate may be, for example, but not limited to, 6.8%, 6.9%, 7% or 7.1%.

[0060] By further optimizing and adjusting the addition amount of the binder and the pore-forming agent, the prepared porous carrier has high strength, a high specific surface area and an ordered mesoporous channel structure.

[0061] In some preferred embodiments, the binder includes but is not limited to at least one of bentonite, attapulgite, diatomaceous earth, kaolin, argillaceous earth, cement, quartz sand, hydroxypropyl methylcellulose, polyvinyl alcohol, sodium carboxymethyl cellulose, styrene-butadiene rubber powder, latex powder or sesbania powder;

[0062] The pore-forming agent includes, but is not limited to, at least one of cellulose powder, ammonium bicarbonate, hydroxypropyl methylcellulose, polyvinyl alcohol, sodium carboxymethyl cellulose, styrene-butadiene rubber powder, latex powder or sesbania powder.

[0063] In some preferred embodiments, the method for preparing the porous carrier comprises: mixing formulated amounts of nano-calcium carbonate, a binder and a pore-forming agent, and then sequentially forming, drying and calcining to prepare the porous carrier.

[0064] The porous carrier prepared by the preparation method has a high specific surface area and an ordered mesoporous channel structure, which can not only promote the dispersion of sulfur element, but also allow sulfur autotrophic denitrifying bacteria to enter the mesoporous channels, thereby fully utilizing the inner surface.

[0065] In some preferred embodiments, the molding method includes but is not limited to disc granulation, extrusion or tableting, or a molding method well known to those skilled in the art.

[0066] The molding process also includes adding 8%-20% water by weight of the raw materials.

[0067] In some preferred embodiments, the drying temperature may be, for example, but not limited to, 120°C, 130°C, 140°C or 150°C;

[0068] The drying time may be, for example, but not limited to, 3 h, 5 h, 7 h, 9 h or 10 h.

[0069] The drying step is performed to remove moisture from the blank.

[0070] In some preferred embodiments, the calcination temperature may be, for example, but not limited to, 350°C, 400°C, 450°C or 500°C;

[0071] The calcination time may be, for example, but not limited to, 3 h, 4 h or 5 h.

[0072] The pore former is removed by calcination to obtain a carrier with a porous structure.

[0073] In a second aspect, the present invention provides a method for preparing the above-mentioned sulfur autotrophic filler, comprising: immersing the porous carrier in a solvent containing elemental sulfur, and preparing the sulfur autotrophic filler after drying.

[0074] The inventors have found that the geometric structure of sulfur molecules (S8) can be changed through the dissolution process. Sulfur is composed of S8 ring molecules in the solid state and chain molecules in the liquid state. Therefore, after sulfur is dissolved in a solvent (such as carbon disulfide), the S8 molecules are converted from solid ring molecules to liquid chain molecules. The conversion of S8 molecules from rings to chains greatly reduces the steric hindrance effect, and can enter the inner pores of the nano-calcium carbonate porous carrier more smoothly, so that sulfur can be more evenly dispersed on the inner surface of the nano-calcium carbonate, improve the dispersibility of sulfur, increase the contact surface area of ​​sulfur and biofilm, reduce the mass transfer resistance in the sulfur autotrophic denitrification process, and improve the denitrification treatment effect.

[0075] In some preferred embodiments, the mass of the carbon disulfide is 2-3 times the mass of elemental sulfur.

[0076] By further optimizing and adjusting the elemental sulfur concentration in the solvent, a sulfur autotrophic filler with a suitable elemental sulfur loading amount can be prepared.

[0077] In a third aspect, the present invention provides the use of the above-mentioned sulfur autotrophic filler in sulfur autotrophic denitrification.

[0078] The filler provided by the invention has high denitrification accuracy, denitrification load and strength, and can be used in sulfur autotrophic denitrification.

[0079] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.

[0080] Example 1

[0081] (1) Preparation of porous carrier:

[0082] ① Molding: Weigh 1000g of nano calcium carbonate, 1g of attapulgite, 50g of cement, 8g of latex powder, and 60g of sodium carboxymethyl cellulose, a total of 1119g. Among them, attapulgite accounts for 0.1wt.% of nano calcium carbonate, cement accounts for 5wt.% of nano calcium carbonate, latex powder accounts for 0.8wt.% of nano calcium carbonate, sodium carboxymethyl cellulose accounts for 6wt.% of nano calcium carbonate, and the total amount of additives accounts for 11.9wt.% of nano calcium carbonate. Among them, the binder accounts for 0.1wt.%+5wt.%+0.8wt.%+6wt.%=11.9wt.% of the nano calcium carbonate; the pore-forming agent latex powder and sodium carboxymethyl cellulose account for 0.8wt.%+6wt.%=6.8wt.% of the nano calcium carbonate. Mix the above raw materials, then roll-form them in a disc granulator, and add water continuously while rolling, with a total amount of 90mL, and roll-form until the particle size is 3-5mm.

[0083] ② Drying: Dry at 120℃ for 10h.

[0084] ③ Calcination: Calcinate at 350℃ for 5h to obtain a porous carrier of nano-calcium carbonate.

[0085] (2) Preparation of sulfur autotrophic filler:

[0086] ① Impregnation: First, the water absorption rate of the above-mentioned nano-calcium carbonate porous carrier is measured to be 40%, then 20g of sulfur is dissolved in 40g of CS2, and the volume is fixed to 40mL after stirring evenly, and then the sulfur-containing solution is loaded on 100g of the above-mentioned nano-calcium carbonate porous carrier by an equal volume impregnation method.

[0087] ② Drying: Finally, air-dry in the air for 10 hours to obtain the finished product of the loaded sulfur autotrophic filler.

[0088] Example 2

[0089] (1) Preparation of porous carrier:

[0090] 1. molding: weigh nano-calcium carbonate 1000g, kaolin 31g, cement 40g, quartz sand 8g of 40-80 purpose, hydroxypropyl methylcellulose 60g, polyvinyl alcohol 5g, styrene-butadiene rubber powder 6g, 1150g in total. Wherein kaolin accounts for 3.1wt.% of nano-calcium carbonate, cement accounts for 4wt.% of nano-calcium carbonate, quartz sand accounts for 0.8wt.% of nano-calcium carbonate, hydroxypropyl methylcellulose accounts for 6wt.% of nano-calcium carbonate, polyvinyl alcohol accounts for 0.5wt.% of nano-calcium carbonate, styrene-butadiene rubber powder accounts for 0.6wt.% of nano-calcium carbonate, and the total amount of additives accounts for 15wt.% of nano-calcium carbonate. The binder accounts for 3.1wt.%+4wt.%+0.8wt.%+6wt.%+0.5wt.%+0.6wt.%=15wt.% of the nano-calcium carbonate; the pore-forming agent hydroxypropyl methylcellulose, polyvinyl alcohol and styrene-butadiene rubber powder account for 6wt.%+0.5wt.%+0.6wt.%=7.1wt.% of the nano-calcium carbonate. The above raw materials are mixed and then rolled in a disc granulator. Water is continuously added during rolling, and the total amount of water added is 230mL. Rolling is carried out until the particle size is 3-5mm.

[0091] ② Drying: Dry at 150℃ for 3h.

[0092] ③ Calcination: Calcinate at 500℃ for 3h to obtain a porous carrier of nano calcium carbonate.

[0093] (2) Preparation of sulfur autotrophic filler:

[0094] ① Impregnation: First, the water absorption rate of the above-mentioned nano-calcium carbonate porous carrier is measured to be 50%, then 30g of sulfur is dissolved in 90g of CS2, and the volume is fixed to 80mL after stirring evenly, and then the sulfur-containing solution is loaded on 100g of the above-mentioned nano-calcium carbonate porous carrier by the method of excessive impregnation.

[0095] ② Drying: Finally, air-dry in the air for 15 hours to obtain the finished product of the loaded sulfur autotrophic filler.

[0096] Example 3

[0097] (1) Preparation of porous carrier:

[0098] ① Molding: Weigh 1000g of nano-calcium carbonate, 10g of diatomite, 40g of cement, 60g of hydroxypropyl methylcellulose, 5g of polyvinyl alcohol, and 5g of latex powder, a total of 1120g. Among them, diatomite accounts for 1wt.% of nano-calcium carbonate, cement accounts for 4wt.% of nano-calcium carbonate, hydroxypropyl methylcellulose accounts for 6wt.% of nano-calcium carbonate, polyvinyl alcohol accounts for 0.5wt.% of nano-calcium carbonate, and latex powder accounts for 0.5wt.% of nano-calcium carbonate. The total amount of additives accounts for 12wt.% of nano-calcium carbonate. Among them, the binder accounts for 1wt.%+4wt.%+6wt.%+0.5wt.%+0.5wt.%=12wt.% of the nano-calcium carbonate; the pore-forming agent hydroxypropyl methylcellulose, polyvinyl alcohol and latex powder account for 6wt.%+0.5wt.%+0.5wt.%=7wt.% of the nano-calcium carbonate. The above raw materials were mixed and then rolled in a disc granulator. Water was continuously added during rolling, with a total amount of water added of 110 mL. The particles were rolled until the particle size was 3-5 mm.

[0099] ② Drying: Dry at 130℃ for 5h.

[0100] ③ Calcination: Calcinate at 400℃ for 4h to obtain a porous carrier of nano calcium carbonate.

[0101] (2) Preparation of sulfur autotrophic filler:

[0102] ① Impregnation: First, the water absorption rate of the above-mentioned nano-calcium carbonate porous carrier is measured to be 50%, then 25g of sulfur is dissolved in 50g of CS2, and the volume is fixed to 50mL after stirring evenly, and then the sulfur-containing solution is loaded on 100g of the above-mentioned nano-calcium carbonate porous carrier by an equal volume impregnation method.

[0103] ② Drying: Finally, air-dry in the air for 12 hours to obtain the finished product of the loaded sulfur autotrophic filler.

[0104] Comparative Example 1

[0105] The sulfur autotrophic filler in the comparative example is the sulfur autotrophic filler currently used in engineering projects, and the filler is formed by pressing sulfur powder, calcium carbonate, binder and other additives by hot pressing.

[0106] Test Example 1

[0107] The specific surface area and pore structure of the sulfur autotrophic filler provided in Example 1 and Comparative Example 1 were tested by the following method:

[0108] The specific surface area of ​​the sulfur autotrophic filler was tested using a JW-BK100 specific surface and pore size analyzer according to the method in GB / T19587-2017 "Determination of the specific surface area of ​​solid substances by gas adsorption BET method".

[0109] The pore structure of the sulfur autotrophic filler was analyzed using a JW-BK100 specific surface and pore size analyzer in accordance with GB / T21650.2-2008 "Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method Part 2: Analysis of mesopores and macropores by gas adsorption method".

[0110] The test results are shown in Table 1.

[0111] Table 1 Summary of specific surface area and pore structure data

[0112]

[0113] The adsorption-desorption performance and pore size distribution of the sulfur autotrophic filler provided in Example 1 and Comparative Example 1 were tested, and the results were as follows: Figure 1-Figure 4 As shown. Among them, Figure 1 ( Figure 1 There are two lines in it, the lower curve represents the adsorption isotherm and the upper curve represents the desorption isotherm) and Figure 2 They are respectively the adsorption-desorption isotherm and pore size distribution curve of the sulfur autotrophic filler provided in Comparative Example 1, Figure 3 ( Figure 1 There are two lines in it, the lower curve represents the adsorption isotherm and the upper curve represents the desorption isotherm) and Figure 4 They are the adsorption-desorption isotherm and pore size distribution curve of the sulfur autotrophic filler provided in Example 1 respectively.

[0114] According to the classification of IUPAC (International Union of Pure and Applied Chemistry), Figure 1 and Figure 3 The N2 adsorption-desorption isotherms of the two materials are all type IV isotherms, indicating that both materials have mesoporous structures. Although the sulfur autotrophic fillers currently used in engineering in the comparative example also have mesoporous structures, the data in Table 1 and Figure 1-Figure 4It can be seen that the pore size distribution of the sulfur autotrophic filler mesoporous material provided in Comparative Example 1 is very uneven, while the pore size distribution of the sulfur autotrophic filler provided in Example 1 is relatively uniform, because: (1) Generally speaking, the closer the average pore size is to the most probable pore size, the more uniform and single the pore distribution is; (2) The peak intensity on the pore size distribution curve represents the number of pores. The higher the ordinate corresponding to a certain pore size, the more pores there are in the pore size; (3) The width of the hysteresis loop is related to the uniformity of the pore size distribution. Generally, the wider the pore size distribution is, the wider the hysteresis loop is; (4) Figure 1 and Figure 3 The hysteresis loops on the adsorption-desorption isotherms all belong to the H3 type of hysteresis loops in the IUPAC classification. Figure 1 It can be seen that the H3 type hysteresis loop isotherm of the sulfur autotrophic filler provided in Comparative Example 1 does not have an obvious saturated adsorption platform, which also shows that its pore structure is very irregular.

[0115] In summary, the sulfur autotrophic filler prepared by the method provided by the present invention is a mesoporous material with a high specific surface area and an ordered mesoporous channel structure, which can not only promote the dispersion of sulfur elements, but also allow sulfur autotrophic denitrifying bacteria to enter the mesoporous channels, thereby making full use of the inner surface.

[0116] Therefore, the present invention loads sulfur on a porous carrier to obtain a sulfur autotrophic filler with a larger specific surface area and a suitable pore structure, which greatly reduces the influence of mass transfer during sulfur autotrophic denitrification and denitrification, thereby improving the denitrification treatment effect.

[0117] Test Example 2

[0118] The strength of the sulfur autotrophic filler provided in Examples 1-3 and Comparative Example 1 was tested, and the testing method was as follows:

[0119] The strength of the sulfur autotrophic filler can be measured by the compressive strength and water abrasion rate indicators. The compressive strength is tested by the DL 3 intelligent particle strength tester according to the method in HG / T 3927-2007 "Industrial Activated Alumina"; the water abrasion rate is tested by the WSZ-20A gyroscopic oscillator according to the enterprise standard method. The specific test method is as follows:

[0120] ⑴ Weigh about 10g of sample and record the data M.

[0121] ⑵Put the weighed sample into a conical flask and add 100mL of deionized water.

[0122] ⑶ Place the conical flask in an oscillator and oscillate for 10 minutes with a speed of 230 rpm and an amplitude of 20 mm.

[0123] (4) After shaking, dry the water at 80℃ for 1h and weigh it (m1) before filtering it with slow filter paper. The dust remains on the filter paper.

[0124] ⑸ Place the filter paper after filtration in an oven at 80℃ and dry it for 2 hours, then weigh it m2.

[0125] ⑹ Calculation formula for water wear rate:

[0126] The denitrification treatment effect of the sulfur autotrophic filler provided in Examples 1-3 and Comparative Example 1 was tested, and the testing method was as follows:

[0127] The denitrification effect of the sulfur autotrophic filler was investigated using a fixed-bed reactor in a small-scale evaluation device. The reactor used was made of acrylic material with an inner diameter of 5.33 cm. The filling height of the sulfur autotrophic filler in the reactor was 13.5 cm, so the filling amount of the sulfur autotrophic filler in each reactor was 300 mL, and the height-to-diameter ratio of the sulfur autotrophic filler bed in each reactor was 13.5 / 5.33=2.5.

[0128] The water treatment volume is 0.3L / h, that is, the liquid hourly space velocity of each reactor (That is, each cubic meter of sulfur autotrophic filler can process 1 cubic meter of water per hour).

[0129] The influent water quality is MBBR test water, and the nitrate nitrogen (NO3 - -N) concentration was 45 mg / L.

[0130] The term liquid hourly space velocity (LHSV) refers to the amount of water treated by a unit volume of catalyst per unit time, referred to as space velocity, with the unit being h. -1 The liquid hourly space velocity can be calculated according to the following formula:

[0131]

[0132] The results show that the sulfur autotrophic filler provided in Examples 1-3 can stably obtain a total nitrogen effluent of less than 4 mg / L, which is far lower than the effluent requirement of 15 mg / L of the first-level A standard. The denitrification treatment effect and strength index are shown in Table 2:

[0133] Table 2 Denitrification effect and some physical indicators of the sulfur autotrophic filler small test evaluation test

[0134] Denitrification accuracy, mg / L <![CDATA[Denitrification load, kgNO3 - -N / m 3 ·d]]> Compressive strength, N / particle Water wear rate, % Example 1 3.3 0.9 143 0.35 Example 2 3.1 1.0 149 0.28 Example 3 3.2 1.0 135 0.31 Comparative Example 15 0.4 58 4.6

[0135] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sulfur autotrophic filler, characterized in that: including a porous support and elemental sulfur; The elemental sulfur is loaded on the porous carrier; The porous carrier is mainly prepared from nano calcium carbonate, a binder and a pore-forming agent; The method for preparing the sulfur autotrophic filler comprises: immersing the porous carrier in a solvent containing elemental sulfur, and drying the solvent to obtain the sulfur autotrophic filler.

2. The sulfur autotrophic filler according to claim 1, characterized in that: The mass of the elemental sulfur is 20%-30% of the mass of the porous carrier; The mass ratio of the binder to the nano calcium carbonate is 11.9%-15%; The mass ratio of the pore-forming agent to the nano-calcium carbonate is 6.8%-7.1%.

3. The sulfur autotrophic filler according to claim 1, characterized in that: The binder comprises at least one of bentonite, attapulgite, diatomaceous earth, kaolin, argillaceous earth, cement, quartz sand, hydroxypropyl methylcellulose, polyvinyl alcohol, sodium carboxymethyl cellulose, styrene-butadiene rubber powder, latex powder or sesbania powder; The pore-forming agent includes at least one of cellulose powder, ammonium bicarbonate, hydroxypropyl methylcellulose, polyvinyl alcohol, sodium carboxymethyl cellulose, styrene-butadiene rubber powder, latex powder or sesbania powder.

4. The sulfur autotrophic filler according to claim 1, characterized in that: The method for preparing the porous carrier comprises: mixing the nano calcium carbonate, the binder and the pore-forming agent in the prescribed amount, and then sequentially forming, drying and calcining to prepare the porous carrier.

5. The sulfur autotrophic filler according to claim 4, characterized in that: The forming method includes disc granulation, extrusion or tableting; The molding process also includes adding 8%-20% water by weight of the raw materials.

6. The sulfur autotrophic filler according to claim 4, characterized in that: The drying temperature is 120-150°C; The drying time is 3-10 hours.

7. The sulfur autotrophic filler according to claim 4, characterized in that: The calcination temperature is 350-500°C; The calcination time is 3-5h.

8. The sulfur autotrophic filler according to claim 1, characterized in that: The solvent includes carbon disulfide; The mass of the carbon disulfide is 2-3 times the mass of elemental sulfur.

9. Use of the sulfur autotrophic filler according to any one of claims 1 to 8 in sulfur autotrophic denitrification.

Citation Information

Patent Citations

  • Method for preparing positive material of lithium-sulfur battery

    CN103123966A

  • High-efficiency coated light biologic ceramsite

    CN2545194Y

  • Composition for removing nitrate nitrogen, etc., and production method therefor

    JP2003071493A

Cited By

  • High-porosity anti-mineralization sulfur autotrophic denitrification filter material capable of slowly releasing trace elements and preparation method of high-porosity anti-mineralization sulfur autotrophic denitrification filter material

    CN121361892A